Isolation and Characterization of Pathogenic Mold Causing Potato Tuber Rot Disease - Rizal Koen Asharo; Reni Indrayanti; Azizatul Amala; Eldrian Daffa Raihan; Raymond Rayhand Tampanguma; Hilda Arsyah Eka Putri; Pinta Omas Pasaribu; Nurul Assyifa Wardana (Jurnal Penelitian Pendidikan IPA, 2024)
The potato plant (Solanum tuberosum L.) is a perennial crop that contains high amounts of carbohydrates, minerals, and vitamins in its tubers, making it a carbohydrate-rich alternative food to rice or corn. One of the diseases that often appear on potato plants is potato rot caused by pathogenic molds. This study aims to isolate and characterize pathogenic fungi that cause blight on potato tubers based on Koch's Postulates. Potato pathogenic molds were isolated from potato tubers that had been rotted, then the molds were grown on PDA and purified twice. The purified isolates were then inoculated onto 30 healthy potato tubers and incubated for 7 days. Healthy potato tubers experienced the same symptoms as potato tuber rot. The isolated pathogenic fungi were then characterized so that the pathogenic fungi of Phytophthora infestans were obtained. In this study, Koch's Postulate method was successfully applied to isolate and characterize the pathogenic fungi that cause potato tuber rot. The pathogenic fungi caused a potato tuber rot disease incidence value of 100% with a disease severity value of 60.7%. The two factors that determine the disease incidence and disease severity values are internal factors (genes and traits of the pathogen) and external factors (environment).